Microbial Metabolites in the Maturation and Activation of Dendritic Cells and Their Relevance for Respiratory Immunity - Wilson, Kayla R.; Gressier, Elise; McConville, Malcolm J.; Bedoui, Sammy (Frontiers in Immunology, 2022)
The respiratory tract is a gateway for viruses and bacteria to invade the human body from the external environment. Critical to the protection against these invaders are dendritic cells (DCs) - a group of highly specialized myeloid cells that monitors the lung microenvironment and relays local information to T cells. Following the recognition of danger signals and/or pathogen molecular associated patterns in the lungs, DCs undergo activation. This process arms DCs with the unique ability to induce the proliferation and differentiation of T cells. Depending on how DCs interact with T cells, the ensuing T cell response can be tolerogenic or immunogenic and as such, the susceptibility and severity of respiratory infections are influenced by the signals DC receive, integrate, and further communicate. It is becoming increasingly clear that these facets of DC biology are heavily influenced by the cellular components and metabolites produced by the lung and gut microbiota. In this review, we discuss the roles of different DC subsets in respiratory infections and how microbial metabolites impact their development, propensity for activation and subsequent activation. In particular, we highlight the consequences these concepts have on respiratory immunity and the questions that still remain.